(In)securitising post-Soviet Space through Security Policies: Russian and the Western Concerns on the Colour Revolutions in Ukraine and Georgia - Fatih YAŞAR; Muharrem DOĞAN (Gazi Akademik Bakış)
This article mainly elaborates the relations between Russia and the West during and after the Cold War. Both sides saw each other as a security threat during the Cold War. After 1990s when the Soviet Union collapsed, this antagonistic relation ended for a short period. Once Vladimir Putin came to power, Russia once again revealed security concerns in the post-Soviet space. The iconic symbol of this concern was the Colour Revolutions in Georgia and Ukraine. The Kremlin saw the Revolutions as a Western threat to Russia’s identity formation in the region. On the other hand, the West saw the Revolutions as a call for democratic liberation for the peoples of the region. Hence, this study looks deeply into both sides of concerns about the Revolutions through the concepts of identity politics and security concerns.